The Effect of Volleyball Training Program on Private Primary and Secondary School’s Students Depression Levels - Gaye Erkmen; Mehibe Akandere; İbrahim Bozkurt; Elif Aycan Atak (Türk Spor ve Egzersiz Dergisi)
The purpose of the study was to investigate the the effect of volleyball training program, as a leisure activity, on students depression levels. The sample of the study consists of 202 students (intervention group), 201 students (control group). Eight weeks training program was prepared and conducted at the intervention group. This study was a pre-test post-test experimental research design with control group. The data of the research were collected with demographic information form and Depression Scale for Children. To revealed that whether there were differences between pretest and posttest depression scores of intervention and control groups ANCOVA analysis was conducted. Results revealed that there was a significant difference between intervention and control group’s students pre-test and post-test depression scores (p = .000). According to ANCOVA findings, students of intervention and control groups pre-test depression scores were controlled, there were significant differences between intervention and control group students’ posttest depression scores (F(2-400) = 821.24, p = .000). It was revealed that volleyball training program have an impact on having a lower depression scores of the students in the intervention group than depression scores of the students in the control group. In this respect, in order to ensure that our children are away from depression and to be healthier individuals in their in physical and spiritual life, their educational processes should be supported by participating sport, physical activities and games. It is considered that students should be directed to various sporting activities by family, school administration and physical education teachers.